Funzione giurisdizionale ed equilibrio dei poteri (Società e diritti, 2022)
The Judiciary, as considered guarantor of the respect for the legality, is currently endowed with almost unlimited powers. The subjectivity of the juridical interpretation and the consequent possibility of abuses, require instead that the balance between the various functions of the State is ensured.